Hubungan Kadar Interleukin-6 terhadap Luaran Mortalitas dan Hari Rawat serta Hari Penggunaan Oksigenasi Tekanan Positif Pasien COVID-19 di RSUP Dr. Sardjito - Kuncoro, Kusuma Edhi; Sudadi; Sari, Djayanti; Wisudarti, Calcarina Fitriani Retno (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: COVID-19 is a disease caused by the SARS-CoV-2 virus with the main clinical manifestations of respiratory disorders. Patients with severe and critical symptoms require oxygenation therapy during treatment. Interleukin-6 (IL-6) plays a role in the course of the disease and is associated with the clinical severity of COVID-19. IL-6 has the potential as one of the test parameters to estimate the outcome of COVID-19 patients. Objective: To know the relationship between IL-6 levels and the outcome of mortality, length of stay (LOS) and positive pressure oxygenation days of COVID-19 patients during hospitalization at Dr. Sardjito hospital. Methods: The study design was a retrospective observational cohort by taking secondary data from the medical records of hospitalized COVID-19 confirmed patients who were examined for serum IL-6 during April 2020- March 2021 at dr.Sardjito Hospital. Data collection was carried out at the Medical Records Instalation of Dr. Sardjito Hospital. The relationship of the IL-6 variable to the outcome was tested by logistic regression method and further analyzed with Kaplan-Meier and Cox regression analysis of survival. Results: There were 302 research subjects with a mean age of 55.45 (+14.79) years, 183 male (60.6%) and 119 female (39.4%). Subjects with IL-6 >80 pg/mL had a higher risk of death than those with IL-6 <80 (p=0.000, HR=4.68). As many as 87.4% of the subject required oxygenation therapies during hospitalization. Group of subjects with an IL-6 value >80 was significantly required more positive pressure oxygenation therapy (p=0.000) and require longer (p=0.005) duration of positive pressure oxygenation (9.36(+5,9) days) compared to the group of subjects with IL-6 <80 (6(+2,98) days). The difference in LOS was significantly different between groups of subjects, with the median LOS for subjects with IL-6 >80 was 25 days, while for subjects with IL-6 <80 was 13 days (p= 0.000). Conclusion: There was a significant relationship of IL-6 levels >80 pg/mL with increased risk of mortality, LOS and the requirement of positive pressure oxygenation therapies in COVID-19 patients.